Effects of zinc and calcium minerals intake on cadmium accumulation in the liver of broiler chicken - Rachmawati, Sri; ., Darmono; Arifin, Zainal (Indonesian Animal Sciences Society, 1999)
Cadmium is a heavy metal which can accumulate in animal tissues, may have an effect the growth of chicken, causes a residual problems and is danger for human consumption. Study on evaluating the effect of mineral zinc (Zn) and calcium (Ca) intake on cadmium (Cd ) accumulation in the liver of broilers and their growth was carried out. One hundred and eighty of day old chicks (DOC) were divided into 6 groups, group I was used as control, group II, III, IV, V and VI were given feed containing of 5 ppm Cd, 5 ppm Cd and 10 ppm Zn, 5 ppm Cd and 15 ppm Zn, 5 ppm Cd and 10 ppm Ca, 5 ppm Cd and 15 ppm Ca respectively in their feed. Cd, Zn and Ca were added as CdCl2, ZnCl2 and CaCl2. During the experiment, at week -0, -1,-2,-3 and -4, five chickens from each group were weighed and then they were slaughtered and livers were collected. The liver samples were analyzed for Cd content by Atomic Absorption Spectrophotometer. The result indicated that Cd exposed to chickens caused the accumulation of that Cd in their liver. The addition of 15 ppm Zn in feed reduced the accumulation of Cd in liver significantly (P<0.05). However the addition of Ca in chicken feed gave greater effect in reducing the Cd accumulation in liver compared to that of Zn supplementation. 10 ppm Ca and 15 ppm Ca in chicken feed caused the accumulation of Cd in liver chicken significantly decreased (P<0.05). Ca supplementation also caused of increasing body weight of chickens. The body weight of five weeks old chickens given 15 ppm Ca in their feed as in average of 1,820 grams is higher than that of chickens in control group, which was 1,761 grams. Whereas the body weight of chickens in group IV, which was given with 15 ppm Zn in their diet was in average of 1,745 grams. It was concluded that Zn and Ca can reduce the accumulation of Cd in broiler chicken liver. Â Key words : Zinc, calcium, accumulation, cadmium